Estimation Of Bioflavonoid Quercetin In Acacia Catechu Ethanolic Leaf Extract By Hplc Method - LAKSHMI.T,; RAJENDRAN. R, (International Journal of Pharma and Bio Sciences, 2012)
Acacia catechu willd (Family: Fabaceae and subfamily: Mimosoideae) known as Black cutch has a diverse pharmacological and phytochemical importance. It is a potent medicinal plant in the traditional Indian medicinal systems. The leaves, bark, heartwood had many nutritional and medicinal uses .The aim of our present study is to investigate the Estimation of Bioflavonoid Quercetin in Acacia catechu Ethanolic Leaf extract by HPLC method.